Application of agent-based paradigm to model corrosion of steel in concrete environment. (19th May 2018) - Poursaee, A.
ABSTRACT: This paper explains developing an agent-based computer model to predict the corrosion of steel bars in the high alkaline environment in concrete. Modelling started with specific assumptions about 'agents', how they interact and how the population changes over time. A simulation approach, employing agent-based modelling, was formulated and corrosion of steel in the alkaline environment of concrete pore solution, with different chloride concentrations, was simulated. The electrochemical behaviour of steel in a chloride-contaminated concrete pore solution was also experimentally examined. Results of the simulations and the experiments were in good agreement.